Structural changes in early-stage Parkinson’s disease with resting tremor at node, edge and network level - Yuke Zhong; Ying Liu; Huahua Su; Hang Liu; Guohui Liu; Zhihui Liu; Jiahao Wei; Junyi Wang; Yuchen She; Changhong Tan; Lijuan Mo; Lin Han; et al. (Brain Research Bulletin)
Background: Resting tremor in Parkinson’s disease (PD) is associated with the activity in the basal ganglia and cerebello-thalamo-cortical circuits/network. However, most insights stem from functional MRI research, and structural studies, which can provide basis for and constrain functional activity, remains limited. Methods: We investigated the structural change in PD patients with resting tremor (PD-WR) from a network perspective. 42 early-stage PD-WR, 27 PD patients without resting tremor (PD-NR), and 56 healthy controls (HC) were included. Results: PD-WR showed lower cortical thickness in several motor-related lobules. Compared to HC, significant atrophy was found in right lobule VIIA (t = -3.076, p = 0.016, Cohen's d = 0.627), left lobule VI (t = -3.323, p = 0.007, Cohen's d = 0.678), and right lobule VI (t = -3.052, p = 0.017, Cohen's d = 0.623) in PD-WR. Compared to PD-NR, left lobule V also had a significant reduction (t = -2.958, p = 0.023, d = −0.657). PD-WR had higher fractional anisotropy in cerebello-cortical connection compared to HC (t = 3.209, p = 0.009, d = 0.926), with reduced radial (t = -2.561, p = 0.046, d = 0.739) and mean (t = 2.614, p = 0.046, d = 0.871) diffusivity compared to PD-NR. At the network level, better hierarchy (rho = 0.598, p = 0.004), small-worldness (rho = 0.621, p = 0.003), and increased nodal involvement of the thalamus (rho = 0.718, p = 0.031) and motor cortex (rho = 0.660, p = 0.055) were positively correlated with tremor amplitude. Conclusion: Our study supports the alternation of the cerebello-thalamo-cortical circuit in PD-WR. However, further research with other forms of PD, a wide range of disease stage and larger sample size is needed.